2017
DOI: 10.1021/acs.iecr.7b02553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of H2O in the Feed of Sulfur Recovery Unit on Sulfur Production and Aromatics Emission from Claus Furnace

Abstract: An increase in the exploitation of sour reservoirs with a high content of acid gas (mainly H 2 S and CO 2 ) and the enforcement of stringent emission standards have triggered demand for high sulfur recovery efficiency in sulfur recovery units (SRUs). The high amount of H 2 O that is present in feed gases to the SRU can act as a diluent in the thermal section of the SRU and can also pose operational difficulties and have substantial chemical effect on the equilibrium-limited reactions of sulfur production and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 34 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…Not to mention, enriched acid gas streams should be free of water as in the presence of water, hydrogen sulfide reacts with iron in the construction material and promotes cracking the infrastructure [18]. Ibrahim et al [23] showed that the presence of water not only worsens the thermal efficiency in the reaction furnace, but also promotes the production of unwanted aromatic hydrocarbons.…”
Section: Process Descriptionmentioning
confidence: 99%
“…Not to mention, enriched acid gas streams should be free of water as in the presence of water, hydrogen sulfide reacts with iron in the construction material and promotes cracking the infrastructure [18]. Ibrahim et al [23] showed that the presence of water not only worsens the thermal efficiency in the reaction furnace, but also promotes the production of unwanted aromatic hydrocarbons.…”
Section: Process Descriptionmentioning
confidence: 99%
“…The overall energy balance equation is as follows: (11) The enthalpy difference is calculated based on the following equation (12) The kinetic energy is calculated based on the following equation: (13) The potential energy is calculated based on the following equation:…”
Section: Energy Balance Equationsmentioning
confidence: 99%
“…Hydrogen Sulphide is used as feed to sulphur recovery plants (SRU) to produce elemental Sulphur [9,10]. The main purpose of SRU plants is to prevent H2S emissions against environmental regulations in the world [11,12,13]. The modified Claus process is the most used one to produce Sulphur [14].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed mechanism used for the Claus furnace simulations has been validated using much experimental data from the laboratory-scale setups and the industrial Claus process plant in the UAE . Its submechanisms on H 2 S, CO 2 , COS, CS 2 , and hydrocarbon were validated successfully in refs and , while the H 2 O submechanism was validated in refs and . However, before using the adopted mechanism to substantiate the role of oxygen concentrations on the emissions of toxic byproducts such as CO and SO 2 in the Claus furnace, it was necessary to validate the CO submechanism using the recent experimental data on CO oxidation in the presence of CO 2 , N 2 , and SO 2 , in order to enhance the reliability of the simulation results.…”
Section: Model Validationmentioning
confidence: 99%